Trend Analysis and Variability of Air Temperature and Rainfall in Regional River Basins - Benjamin Nnamdi Ekwueme; Jonah Chukwuemeka Agunwamba (Civil Engineering Journal, 2021)
Global warming and climate variability are emerging as the foremost environmental problems in the 21st century, especially in developing countries. Full knowledge of key climate change variables is crucial in managing water resources in river basins. This study examines the variability of air temperature and rainfall in the five states of South-Eastern region of Nigeria, using the trend analysis approach. For this purpose, temporal trends in annual rainfall and temperature were detected using non-parametric Mann-Kendall test at 5% significance level. The time series rainfall and temperature data for the period 1922-2008 were analyzed statistically for each state separately. The results of Mann Kendall test showed that there is trend in rainfall in all the capital cities in South-East except Owerri and Awka. It is also observed that the trend of rainfall is decreasing for all the study areas in South-East with the lowest trend rate of -0.1153 mm rainfall occurring in Umuahia. In the case of air temperature, it is observed that the trend is increasing for all the study areas in South-East with the highest trend rate of 0.04698 oC/year occurring in Enugu. These findings provide valuable information for assessing the influence of changes on air temperature and rainfall on water resources and references for water management in the South-Eastern river basin of Nigeria. It also proved that Mann-Kendall technique is an effective tool in analyzing temperature and rainfall trends in a regional watershed. Doi: 10.28991/cej-2021-03091692 Full Text: PDF